Disseminated nocardiosis mimicking exacerbation of pulmonary sarcoidosis - Zuk, J.; Bazan-Socha, S.; Zarychta, J.; Leclercq, A.; Lecuit, Marc; Le Flèche-Matéos, A.; Orlowska-Heitzman, J.; Musial, J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Nocardiosis is a rare, mixed suppurative and granulomatous, bacterial infection that can affect various organs, but most commonly lungs.Clinical manifestation is usually uncharacteristic; can mimic fungal, parasitic and mycobacterial infections or malignancy. Presentation can be also similar to that of the other granulomatous diseases, among them sarcoidosis.We present an unusual case of disseminated nocardiosis in a patient diagnosed before with sarcoidosis and treated with glucocorticoids. Clinical symptoms initially mimicked exacerbation of pulmonary sarcoidosis. The course of disease was severe.